IPTU e progressividade fiscal - Campello, Geórgia Teixeira Jezler (2017)
This work analyzes the main aspects of the fiscal progressiveness in IPTU, given the relevance of the matter, but with no intention of exhausting the subject. The exhibition begins with a brief presentation of the ideas of science, system and juridical system, the connection between the interpretation of the Constitution and the emanated values of the system and the metalinguistic function of the principles. Firstly, it will trace the origin and the evolution of the society, the state model and the role of taxation and progressiveness in this context. Afterwards, the equality is analyzed as a central element of the theories of the justice and as a nuclear principle of the constitutional system that has the contributive capacity as its representation in the tax field. The study also focuses the concept of contributive capacity, its conceptions – subjective and objective – nature of principle and relation with associated and unassociated taxes. Soon afterwards, it presents the tax progressiveness, its nature, juridical foundation and fiscal and extra fiscal aspects, the difference between the fiscal progressiveness and proportionality to demonstrate that the fiscal progressiveness is a sub-principle of the contributive capacity. Yet, it shows the relation between the progressiveness and the fundamental rights, of which elapses the observance to the existential minimum and to the prohibition on confiscation. Eventually, it expatiates on the criterion of rule array of tax incidence in IPTU and the parameters of variation of tax rates applicable to the mentioned tribute, thoroughly analyzing aspects related to the fiscal progressiveness in IPTU. Then, it starts analyzing jurisprudence of Federal Supreme court on the theme. Based on the presuppositions delineated in the research, it demonstrates that the contributive capacity in IPTU refers to an objective manifestation of the taxpayer's wealth and that the tax already admitted application of progressive rates, even before the Constitutional Amendment n.29/00, with lack of usefulness the classification of the taxes in real and personal